Network and 16S rRNA Sequencing-Combined Approach Provides Insightal Evidence of Vitamin K2 for Salt-Sensitive Hypertension - Liu, Tian-hao; Chen, Ming-hao; Tu, Wan-qing; Liang, Qiu-er; Tao, Wen-cong; Jin, Zhen; Xiao, Ya; Chen, Li-guo (Frontiers in Nutrition, 2021)
Vitamin k2 (VK2), found to act to treat hypertension, which has been widely used in the food and pharmaceutical industries nowadays. However, the potential targets and molecular mechanisms of VK2 for salt-sensitive hypertension have not been fully investigated. Therefore, the study aimed to investigate the potential molecular mechanisms of VK2 for salt-sensitive hypertension using network pharmacology and 16S rRNA sequencing strategy. The network pharmacology-based findings from KEGG enrichment analysis revealed that VK2 treated salt-sensitive hypertension were mechanically associated with the complement and coagulation cascades, calcium signaling pathway, renin-angiotensin system, etc. A total of 29 different bacteria in animal experiment after VK2 supplementation were screened and functionally enriched using PICRUSt2. Additionally, 10 signaling pathways were identified in which the renin-angiotensin system was found to be the potential molecular mechanisms with the greatest change multiple and statistical significance. Moreover, the results of the renin-angiotensin system-related proteins expression exhibited VK2 inhibited renin-angiotensin system in salt-induced hypertensive mice, which significantly verified the previous biological and functional prediction analysis. Finally, spearman correlation analysis showed the different bacteria such as Dubosiella, Ileibacterium, ect. had a positive or negative correlation with renin-angiotensin system-related proteins in salt-induced mice. In conclusion, the potential molecular mechanisms of VK2 for salt-sensitive hypertension may be beneficially achieved by the specific inhibition of renin-angiotensin system, contributing to the development for a new preventive strategy of salt-sensitive hypertension.